Safety of garden-stuffs of egg-plant depending on terms of storage - Зінченко, Є. В. (Scientific Progress & Innovations, 2012)
The brought results over of safety garden-stuffs of eggplant of different subspecies’s and type of sort, that kept under various conditions and types of container. Found out the optimal terms of storage of egg-plant with the minimum natural losses of mass of garden-stuffs and to the greater standard product output. Ways of storage of fruits of an eggplant of different subspecies and type of sort, and their influence on a chemical compound after each period of storage are studied. Efficiency of use of different kinds of packing and storage conditions for a concrete investigated grade is proved.